1997
DOI: 10.1111/j.1745-4565.1997.tb00195.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gamma Irradiation on the Lipid Peroxidation in Chicken, Lamb and Buffalo Meat During Chilled Storage

Abstract: Chicken, lamb and buffalo meat were subjected to low‐dose gamma irradiation (2.5 kGy) and stored at 0–3C. Lipid peroxidation in terms of thiobarbituric acid (TBA) number and carbonyl content were monitored during storage. While irradiated meat showed slight increase in TBA number and carbonyl content on storage as compared to nonirradiated meat, this did not affect the sensory qualities of meat. Free fatty acid content decreased markedly on irradiation. Irradiated meats were microbiologically safe and sensoril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
3
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 20 publications
0
14
3
3
Order By: Relevance
“…After 12 months of storage, the total acidity of packaged luncheon (nirsp-nirp) was significantly higher than those of (nirsp-irp, irspnirp or irsp-irp) samples. The results are in contrast with those of Kanatt et al (1997) who indicated that FFA content in meat decreased after irradiation and those of Paul et al (1998) who found that addition of antioxidants prior to R ¼ rejected.…”
Section: Effect Of C-irradiation On Chemical Quality Of Luncheon Meatcontrasting
confidence: 85%
“…After 12 months of storage, the total acidity of packaged luncheon (nirsp-nirp) was significantly higher than those of (nirsp-irp, irspnirp or irsp-irp) samples. The results are in contrast with those of Kanatt et al (1997) who indicated that FFA content in meat decreased after irradiation and those of Paul et al (1998) who found that addition of antioxidants prior to R ¼ rejected.…”
Section: Effect Of C-irradiation On Chemical Quality Of Luncheon Meatcontrasting
confidence: 85%
“…The high oxidation potential of fatty acids present in MDPM resulted in generation of secondary products of fatty acid auto-oxidation such as aldehydes, ketones, hydrocarbons, esters, fuirans and lactans. These products are probably responsible for flavor deterioration during storage (Froning, 1995;Kannat, Paul, Souza, & Thomas, 1997;Ladikos & Lougovois, 1990). The addition of antioxidants to the beef patties significantly (P < 0.05) increased the flavor scores of patty formulas prepared with MDPM (200 g/kg) during the frozen storage period.…”
Section: Sensory Attributesmentioning
confidence: 99%
“…Use of chemical preservatives results in adverse effect on technological properties of casing and problem of toxic residues (Labie, 1987 Radiation processing is a useful technique to improve microbiological quality and to enhance safety of several food commodities by killing pathogens such as Salmonella, Staphylococcus aureus, Campylobacter, Listeria monocytogenes (Farkas, 1998). Previous studies in our laboratories have shown that irradiation treatment can improve shelf life and microbiological quality of buffalo, chicken and lamb meat stored in chilled state (Kanatt, Paul, DÕsouza, & Thomas, 1997;Naik, Paul, Chawla, Sherikar, & Nair, 1994;Paul, Venugopal, & Nair, 1990).…”
Section: Introductionmentioning
confidence: 97%